Kinetic analysis of the chemical processes in the decomposition of gaseous dielectrics by a non-equilibrium plasma - part 1: CF4 and CF4/O2 - Bauerfeldt Glauco F.; Arbilla Graciela (Journal of the Brazilian Chemical Society, 2000)
Numerical integration of the coupled differential equations which describe a chemical reacting system and sensitivity analysis are becoming increasingly important tools in chemical kinetics. In this work, a numerical modelling analysis of the chemical processes in the gas-phase decomposition of pure CF4 and CF4/O2 mixtures, in the presence of silicon, was performed. The relative importance of individual processes was analysed and the sensitivity coefficients as well as the effect of the parameters uncertainties were determined . The results were compared with experimental data from the literature to adjust the model parameters. The main etching agent in the system is the fluorine atom. The concentrations of the main species (SiF4, CO, CO2 and COF2) depend on the composition of the mixture.